Preparation of Quercetin/Copper Nanoparticles and Their Preservation Performance on Shine Muscat Grapes - Kundian Che; Zhanjun Chen; Luo Weng; Baogang Zhou; Wei Gao; Ran Liu; Jialin Yang; Haoyuan Luo; Wenzhong Hu (Molecules)
Deterioration in fruits represent a significant challenge to food safety, which has prompted our investigation into sustainable fruit preservation technologies. This paper presents the synthesis of quercetin/copper nanoparticles (QC NPs) and their application in the preservation of Shine Muscat grapes. The QC NPs, prepared through quercetin/copper complexation, exhibited stability with a particle size of 79.4 ± 3.2 nm and a zeta potential of −34.00 ± 4.98 mV. The nanoparticles exhibited robust antioxidant activity and 100% bactericidal effect against E. coli and S. aureus at 0.05 mg/mL, thereby underscoring their potential for use in fruit preservation. The application of a sodium alginate (SA) + QC NP coating to Shine Muscat grapes resulted in an 8.08% reduction in weight loss in comparison to the control, which exhibited a 10.40% reduction. The coating maintained firmness and preserved titratable acid content, thereby extending the storage life of the grapes. These findings position QC NPs as a promising material in eco-friendly and effective fruit preservation, and offer a viable solution to postharvest fruit preservation.